Moving beyond voice in children and young people's participation. Issue 1 (March 2017) - Johnson, Vicky
This paper introduces research that challenges decision-makers to listen to and act upon children and young people's evidence. The data come from revisits, 10 years after research ended, to participatory action research processes in Nepal and the UK in which children and young people's (CYP) voices and opinions were surfaced for community decision makers. I sought to understand if and how children and youth input was valued and acted upon by adults. Each case rested on the same value proposition: that inclusion of children and youth is critical to participatory democracy and so incorporating their views can move societies towards improved policies and services for CYP and a culture of mutual respect in intergenerational relationships. The paper focuses on Nepal but draws on analysis across the cases. The revisit revealed that decision-makers in some – but not all – cases were influenced by children and youth. Building on the positive cases, the article describes a tool and process – the Change-scape Framework – that facilitates intergenerational dialogue. It helps link child and youth agency and insights to community decision-making and wider social change. The framework provides a CYP focus to PAR. Creating participatory spaces and building dialogue and trust between children and adults are necessary preconditions for child and youth-centered transformational change.